2018
DOI: 10.1186/s13063-018-2916-9
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ reasoning regarding the decision to participate in clinical cancer trials: an interview study

Abstract: BackgroundClinical cancer trials are crucial for the implementation of new treatments in the clinical setting, but it is equally crucial that patients are given the opportunity to make a well-informed decision about participation. The inclusion process is complex, including both oral and written information about the trial. The process of patients’ decision-making regarding clinical cancer trials has not yet been sufficiently studied. This interview study aims to explore the process of patients’ reasoning rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…This was linked to two core categoriesthe 'trusting relationship' between patient and professional who were united in 'fighting cancer'. Consistent with other study findings [6], both patients and professionals viewed the offer to participate in a clinical trial as the 'only hope in the room'. For some patients, it is hope, and continuing to believe that a cure is possible, that helps to bring some normality to their situation and enables them to cope with a bleak prognosis [35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was linked to two core categoriesthe 'trusting relationship' between patient and professional who were united in 'fighting cancer'. Consistent with other study findings [6], both patients and professionals viewed the offer to participate in a clinical trial as the 'only hope in the room'. For some patients, it is hope, and continuing to believe that a cure is possible, that helps to bring some normality to their situation and enables them to cope with a bleak prognosis [35].…”
Section: Discussionsupporting
confidence: 87%
“…This process is crucial, allowing patients to make a voluntary and autonomous decision as to whether participation is right for them [4]. Similarly, it is imperative participants understand the uncertainty or clinical equipoise involved, with alternative opportunities made fully available to them [5] -such as supportive care within a palliative context [6]. As early phase trials involve patients nearing the end of life and often promise little clinical benefit, [7] decision making presents a highly complex and ethically challenging situation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate a gap between patients’ perceived understanding and physicians’ assessment of patient understanding. Studies have also shown that patients may base their decision to participate in a clinical trial on inadequate facts and misunderstandings [4, 29, 30], although they consider themselves to understand the trial information. In order to improve patient understanding of clinical trials, several kinds of interventions have been shown to be effective: enhanced consent documents, decisional aids and extended consent conversations seem to be of particular interest [9, 31].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the oral and written patient information is to convey information that enables the patient to reach a level of understanding from which a decision can be taken based on study design, impact and risk-benefit combined with the patient’s individual preferences. In oncology as well as in other medical specialties, however, the trial information is often extensive and its communication is a complex process, which may indeed counteract the actual intent of complete information and full understanding [24].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians and nurses found that a most difficult challenge was end-of-life patients eager to participate in all kinds of cutting-edge drug trials, often with an unrealistic hope for possible gain. The patients sometimes had high expectation concerning benefits [17][18][19][20][21][22], or believed the trials were miracles waiting to happen [23]. Though questionable, many physicians found it important to uphold hope and to support a belief in clinical trials because it can benefit patients and relatives.…”
Section: Introductionmentioning
confidence: 99%